[OP.7A.07] TRENDS IN HYPERTENSION AMONG POOR FRENCH CARIBBEAN, 2003 TO 2014: BETTER BUT STILL NOT GOOD ENOUGH. (September 2016) - Carrère, P.; Halbert, N.; Hélène-Pelage, J.; Lang, T.; Inamo, J.; Atallah, A.
Abstract : Objective: The French West Indies are exposed to high rates of cardiovascular-related early mortality and are among the most impoverished French territories. In 2001–03, the PHAPPG study highlighted poor management and control of hypertension in a disadvantaged Guadeloupean population. Since then, new processes of healthcare coordination and a pay-for-performance system have been developed. We aimed to assess changes in hypertension characteristics among poor Guadeloupeans in the last ten years. Design and method: We used data from the PHAPPG-2003 study and conducted a cross-sectional study in 2014 using the same methods. The source population consisted of all Guadeloupeans receiving a systematic periodic health examination funded by social security during the study periods. For better comparability, only beneficiaries of universal health coverage aged 18–64 were finally included (1868 subjects in 2001–03 and 2014 subjects in 2014). Hypertension was defined by antihypertensive treatment or mean of two measurements of blood pressure > = 140/90 mmHg. The 2001–03 and 2014 data were age-adjusted and changes were tested using logistic regression. Results: The prevalence of hypertension slightly decreased, from 38.3% in 2001–03 to 34.5% in 2014 (p = 0.008). The increase in hypertension awareness was larger for women (from 48.3% to 55.3% - p = 0.049) than for men (from 28% to 31.1% - p = 0.419). Among hypertensives who were aware of their condition, the treatment rate increased for women (from 83.1% to 88.3%) but decreased for men (from 80.2% to 75.8%), and that led to a significant difference between sexes in 2014. Controlled hypertension among treated patients increased in both women (from 35.2% to 49.2% - p = 0.013) and men (from 12.9% to 30.1% - p = 0.017). Conclusions: Among these poor French Caribbean with complete health coverage, control of hypertension remained far below national and European goals. Patient awareness and treatment had not improved in men. More effective strategies against cardiovascular risk must be developed in France, especially for men and for patients in the poorest communities.